Wound building : dispatches from the latest disasters in UK poetry - Hayward, Danny (punctum books, 2021)
"Wound Building is a volume of essays, with digressions, on one group of contemporary poets active in a self-organizing political poetry scene in the UK, most of whom have little to no audience outside of the little magazines that they publish and the reading series they put on. The book is a front-line report on the rapid development of this poetry in the period between 2015 and 2020, with a particular focus on the relationship of poetry to violence and its representation ... Ultimately, Hayward argues that the lessons this poetry teaches is never to write a "worthy" narrative when a fucked up collage will do. Rather than a cohesive "account" of a "school" of poets, or a "contribution" to the boring tittle-tattle of aesthetic debates over British poetry as an institution, Wound Building is a front-line report on the local disasters of a contemporary UK poetry caught in the grip of the historical cataclysm of capitalist culture. Wound Building is further concerned with aesthetic problems related to Marxism, anarchism, contemporary trans politics, and class, though its "theoretical" preoccupations are subordinated to its desire to provide a ground-level view on the writing itself, its production, its intellectual aporia, and the ways it finds itself outstripped by the ongoing "march of events" ... "--From publisher's description.